Penerapan Metode Bermain Peran dalam Belajar Pendidikan Agama Islam untuk Meningkatkan Minat Belajar Siswa SMA Mandala Trikora - I Putu Resa Nugroho; Muhamad Thoif; Izzatul Laili (Pusat Riset dan Inovasi Nasional, 2024)
This research is motivated by persistent problems in the Islamic Religious Education (PAI) learning process, particularly related to the lack of variety in teaching methods used by teachers, resulting in low student learning interest. PAI learning plays a crucial role in shaping students' understanding, attitudes, and character in accordance with Islamic values. Therefore, more active and innovative learning strategies are needed to enable students to engage directly in the learning process. This study aims to determine how student learning interest changes in Islamic Religious Education learning through the implementation of role-playing methods at SMA Mandala Trikora Jayapura. The research method used in this study is a qualitative research method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation to obtain a comprehensive picture of the learning implementation and student responses to the role-playing method. The results of the study indicate that the application of role-playing methods in Islamic Religious Education learning can increase student learning interest, foster enthusiasm and active participation in learning activities, and help students understand the learning material more deeply, especially in Islamic history. Thus, the use of varied and interactive learning methods such as role-playing methods can be an alternative, effective learning strategy in improving the quality of Islamic Religious Education learning.